FAKTOR PENYEBAB KETIDAKAKTIFAN KADER POSYANDU - Sunaeni, Sunaeni; Lestaluhu, Santi Aprilian; Pratamaningtyas, Susanti; Soumokil, Octovina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The activity and participation level of Posyandu cadres are expected to have a significant impact on community involvement in Posyandu activities. In implementing Posyandu activities, the availability of an adequate number of cadres is a key factor in ensuring that the entire range of services can run optimally. The purpose of this study was to determine the factors causing the inactivity of Posyandu cadres. The research design used in this study was cross-sectional. The research was conducted in 10 Posyandu. The research was conducted in January 2025. The population consisted of all cadres from 10 predetermined Posyandu. The sample consisted of 115 people. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between knowledge (p value: 0.034) and intensity (p value: 0.00) and cadre activity. It is recommended that cadres increase their awareness of the importance of their role in Posyandu and that cadres are needed, so that strong support and commitment from local governments are required to empower cadres as health workers. Keywords: Cadre, Intensive, Knowledge.